The The Influence of Service Quality, Trust, and Corporate Image on Customer Retention - Albert William, Aloysius; Widayatmoko, Widayatmoko; Setyanto, Eddy (JURNAL KEWIRAUSAHAAN, AKUNTANSI DAN MANAJEMEN TRI BISNIS, 2025)
This research aims to determine the influence of Service Quality, Trust, and Corporate Image on Customer Retention at Young Coffee & Food in Bekasi city. The study utilizes a quantitative approach with both primary and secondary data sources. The population of this study consists of customers of Young Coffee & Food in Bekasi, totaling 478. The sample size is 83 respondents. The sampling technique employed is purposive sampling, selecting customers of Young Coffee & Food who have made at least one purchase transaction. Data analysis was conducted using SPSS version 25.The results of the partial test (t-test) indicate that service quality, trust, and corporate image have a positive and significant influence on customer retention at Young Coffee & Food in Bekasi city. In the partial test, the dominant independent variable affecting customer retention is corporate image, with the largest beta value of 0.244 and a significance value of 0.000, which is less than 0.05. The simultaneous test results (F-test) demonstrate that service quality, trust, and corporate image simultaneously influence customer retention at Young Coffee & Food in Bekasi city.